Powody utrzymywania gotówki w przedsiębiorstwie i ich relacja do ryzyka - Michalski, Grzegorz ("Risk Based Demand for Cash in a Firm", 2007)
Maximization of wealth of his owners is the basic financial aim in management of an enterprise. Cash management must contribute to realization this aim. The article presents the method of determination precautionary and speculative levels of cash in a firm. Level of cash in a firm increases net working capital and costs of holding cash. Both of them decrease value of the firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 365-375